A moral critique of development: ethics, aesthetics and responsibility - Giri, Ananta Kumar; Ufford, Philip Quarles Van (2004)
The discourse and practice of human development has been subjected to fundamental restructuring and criticism in recent years. While restructuring has involved a continuing shift from state to market as the main actor of development, deconstruction of it has led to a critique of development as hegemony and domination. In this context the paper submits that neither a one-sided valorization of development in terms of being a slave to the market nor an essentialist abandonment of development as domination is helpful at the contemporary juncture. The urgent task now is to come to terms with the calling of responsibility which calls for a multi-dimensional approach understanding the simultaneous significance of self, social movements, state and market. Responsibility involves both capacity to look up to the face of the other and self-cultivation-both ethics and aesthetics. In this way the paper presents the outline of a moral critique of development. - Reproduced.
Keywords: Aesthetics; Ethics; Human development